Vulnerability of different nerves to intrafascicular injection by different needle types and at different approach angles: a mathematical model. Issue 4 (27th January 2020) - Sanromán-Junquera, Margarita; Boezaart, Andre; Zasimovich, Yury; Nin, Olga C; Sala-Blanch, Xavier; De Andres, Jose; Reina, Miguel A
Abstract : Background and objectives: We assume that intrafascicular spread of a solution can only occur if a large enough portion of the distal needle orifice is placed inside the fascicle. Our aim is to present and evaluate a mathematical model that can calculate the theoretical vulnerability of fascicles, analyzing the degree of occupancy of the needle orifice in fascicular tissue by performing simulations of multiple positions that a needle orifice can take inside a cross-sectional nerve area. Methods: We superimposed microscopic images of two routinely used nerve block needles (22-gauge, 15° needle and 22-gauge, 30° needle) over the microscopic images of cross-sections of four nerve types photographed at the same magnification. Fascicular tissue that was overlapped between 80% and 100% by a needle orifice was considered at risk to possible intrafascicular injection. The effect of three angular approaches was evaluated. Results: There were statistical differences between the vulnerability of fascicular tissue depending on nerve type, the bevel angle of the needle and the angle approach. Fascicular vulnerability was greater in nerve roots of the brachial plexus after using a 22-gauge 30° needle, as was choosing a 45° angle approach to the longitudinal axis of the nerve. Conclusions: Our results suggest that clinicians may want to consider needle insertion angle and bevel type as they perform peripheral nerve blocks. Furthermore, researchers may want to consider this mathematical model when estimating vulnerabilities of various nerves, needle types and angles of approach of needles to nerves.